Human papillomavirus: What we know and what we doing? - Akarsu, Gökhan Doğukan; Akarsu, Rukiye Höbek; Sungur, Neslihan; Tufanoğlu, Nur (Archives of Community Medicine and Public Health, 2023)
Aim: In this study, it was aimed to determine the thoughts and attitudes of young adults about HPV and HPV vaccines. Methods: This study was planned as a cross-sectional study to determine the knowledge levels and attitudes of young people living in a settlement in the middle of Turkey about the HPV vaccine. The research was conducted with 870 young adults between 1-30 November 2022. Results: The average age of the young people participating in the study was 20.49 ± 2.15 years, 60.9% of them were male. 61% have not heard of the PAP-Smear test before, 51.3% do not know what HPV is, only 17.7% have HPV by vaccination, 8% have HPV vaccine, 24.75% 37.9% of them stated that they wanted to have the HPV vaccine and that the HPV vaccine should be free of charge. Conclusion: It was determined that the knowledge level of young adults about HPV and HPV vaccine, in general, was very low, only one out of four people wanted to be vaccinated against HPV, and the rate of vaccination was very low. Even if the vaccine is free in our country, it is thought that the vaccination rates will be low.